2018
DOI: 10.1002/ccd.27518
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter versus surgical aortic valve replacement in patients at low surgical risk: A meta‐analysis of randomized trials and propensity score matched observational studies

Abstract: In patients who are at low surgical risk, TAVR seems to be associated with increased mortality risk. Until more data in this population is available, SAVR should remain the treatment of choice for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 28 publications
(58 reference statements)
1
34
0
Order By: Relevance
“…Surgical aortic valve replacement (SAVR) was once the only treatment for severe aortic stenosis, but it was often contraindicated in elderly patients because of their age, the severity of aortic stenosis, and comorbidities [3]. Data from developed countries have shown that about one-third of patients with severe aortic stenosis are unable to undergo surgical thoracotomy because of their high surgical risk, or because of contraindications to surgery and anesthesia [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical aortic valve replacement (SAVR) was once the only treatment for severe aortic stenosis, but it was often contraindicated in elderly patients because of their age, the severity of aortic stenosis, and comorbidities [3]. Data from developed countries have shown that about one-third of patients with severe aortic stenosis are unable to undergo surgical thoracotomy because of their high surgical risk, or because of contraindications to surgery and anesthesia [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in TAVR device design, delivery systems and operator experience have led to increasing adoption of TAVR in low-risk patient populations [6,11]. Despite a lack of supporting clinical data, it is conceivable that a less invasive transcatheter approach may provide a safe and effective alternative to SAVR.…”
Section: Discussionmentioning
confidence: 99%
“…To date, registry data examining low-risk patients undergoing TAVR has demonstrated mixed results [6]. A prior meta-analysis comparing TAVR and SAVR in this population suggested a higher 2-year mortality-rate following TAVR, despite similar short-term outcomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…LVEF improvement seems to be the same between TAVI and SAVR; but in patients with low baseline LVEF (< 40%) the improvement may be grater after TAVI than after SAVR. Witberg et al [15] made a systematic review and meta-analysis on the relative risks and benefits of TAVR vs. SAVR in patients who are at low surgical risk. TAVI and SAVR resulted equivalent in short-term mortality but, in intermediate term mortality, TAVI showed increasing mortality rates compared to SAVR suggesting that TAVI should not be performed in this population.…”
Section: Discussionmentioning
confidence: 99%